2013
DOI: 10.1089/cyber.2012.0509
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Purchases and Trust: The Mediating Effect of Stickiness and the Mental Budgeting Account

Abstract: Impulse purchasing is a pervasive yet relatively little-discussed phenomenon. This study investigates the effect of impulse purchases on trust, as well as the mediating effect of stickiness and the mental budgeting account in the group buying context. Questionnaires were sent to group buying participants. The results show that impulse purchases have a positive effect on trust and that both stickiness and the mental budgeting account present a mediating effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Sharma et al (2014) found that general consumer impulsiveness reduces the level of perceived risk. Moreover, in the context of group buying online, impulse purchases were shown to have a positive effect on trust (Wu et al, 2013). Thus, based on the preceding discussion, we hypothesize the following: H1a.…”
Section: Impulse Buying Tendency and Situational Factorsmentioning
confidence: 83%
“…Sharma et al (2014) found that general consumer impulsiveness reduces the level of perceived risk. Moreover, in the context of group buying online, impulse purchases were shown to have a positive effect on trust (Wu et al, 2013). Thus, based on the preceding discussion, we hypothesize the following: H1a.…”
Section: Impulse Buying Tendency and Situational Factorsmentioning
confidence: 83%
“…Hulteń and Vanyushyn (2011) discovered that attractive and eye-catching displays have direct influence on buyer impulsive behavior. The influence of retailing and exclusive displays on impulsive shopping behavior is universal phenomenon (Beatty & Ferrell, 1998;Dholakia, 2000;Hulteń & Vanyushyn, 2011;Mattila & Wirtz, 2008;Wu, Chen, & Chien, 2013;Xiao & Nicholson, 2011).…”
Section: Store Environment and Impulse Buying Tendencymentioning
confidence: 99%
“…The examination of the relationship between mental budgeting and impulse buying bears important theoretical implications as well. Although the impact of impulse buying on mental budgeting has been explored before and researchers have shown that impulse buying has a positive effect on mental budgeting (Wu et al, 2013), this research demonstrated that the relationship between impulse buying and mental budgeting could be bidirectional, such that the increase of mental budgeting could also influence subsequent impulse buying behaviors. Such a finding advances the literature in consumer decision making in general, and mental budgeting and impulse buying in particular.…”
Section: Discussionmentioning
confidence: 77%
“…Booth attractiveness was measured by the 18-item six-dimensional scale developed from Study 1. Mental budgeting was measured by four items from Wu et al (2013). Impulse buying was measured by four items from Beatty and Ferrell (1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation